Organic superbase t-Bu-P4-catalyzed demethylations of methoxyarenes. Issue 14 (16th May 2022) - Shigeno, Masanori; Hayashi, Kazutoshi; Korenaga, Toshinobu; Nozawa-Kumada, Kanako; Kondo, Yoshinori
Abstract : The organic superbase t -Bu-P4 catalyzes the demethylation reactions of methoxyarenes in the presence of alkanethiol and hexamethyldisilazane. Abstract : Herein, we report that the organic superbase t -Bu-P4 catalyzes the demethylation reactions of methoxyarenes in the presence of alkanethiol and hexamethyldisilazane. The system can efficiently convert a variety of substrates, including electron-deficient, -neutral, and -rich substrates and heteroaromatic substrates, and displays excellent functional group tolerance. Computational studies show that the high reactivity achieved by t -Bu-P4 is due to the formation of the nucleophilic naked thiolate species.